Diabetic Retinopathy Blood Vessel Detection Using CNN and RNN Techniques - Whardana, Adithya Kusuma; Rentelinggi, Parma Hadi; Timothy, Hezkiel Dokta (Journal of Information Technology and Cyber Security, 2023)
This research aims to detect diabetic retinopathy using Convolutional Neural Network (CNN) and Recurrent Neural Network (RNN). The main objective is to compare these two methods in detecting the condition. Based on the study’s result after training 10 times on each method, the accuracy results were 92% for the CNN method and 50% for the RNN method. These results show, this study with the dataset used, the CNN method is much more effective in detecting diabetic retinopathy than the RNN method. The CNN method is better due to its ability to extract spatial features from images, which is important in image classification tasks.